Comparative Transcriptome Analysis of Hard and Tender Fruit Spines of Cucumber to Identify Genes Involved in the Morphological Development of Fruit Spines - Lv, Duo; Wang, Gang; Zhang, Qi; Yu, Yao; Qin, Pei-Chao; Pang, Jin-An; Sun, Jing-Xian; Zhang, Ke-Yan; He, Huan-Le; Cai, Run; Pan, Jun-Song (Frontiers in Plant Science, 2022)
The spines of cucumber fruit not only have important commercial value but are also a classical tissue to study cell division and differentiation modes of multicellular trichomes. It has been reported that CsTs (C-type Lectin receptor-like kinase) can influence the development of fruit spines. In this study, we took a pair of cucumber materials defined as hard (Ts, wild type) and tender spines (ts, mutant) and defined the developmental process of fruit spines as consisting of four stages (stage I to stage IV) by continuously observing by microscope and SEM. Comparisons of transcriptome profiles at different development stages of wild-type spines showed that 803 and 722 genes were upregulated in the stalk (stage II and stage III) and base (stage IV) development stages of fruit spines, respectively. The function analysis of DEGs showed that genes related to auxin polar transport and HD-ZIP transcription factor are significantly upregulated during the development of the stalk. bHLH transcription factors and cytoskeleton-related genes were significantly upregulated during the development of the base. In addition, stage III is the key point for the difference between wild-type and mutant spines. We detected 628 DEGs between wild type and mutant at stage III. These DEGs are mainly involved in the calcium signaling of the cytoskeleton and auxin polar transport. Coincidentally, we found that CsVTI11, a factor involved in auxin signal transmission, can interact with CsTs in vivo, but this interaction does not occur between CsVTI11 and Csts, further suggesting that CsTs may regulate the development of fruit spines by influencing cell polarity. These results provide useful tools to study the molecular networks associated with cucumber fruit spine development and elucidate the biological pathways that C-type Lectin receptor-like kinase plays in regulating the development of fruit spines.